Comprehensive Assessment of Outcomes From Patients With Severe Early-onset Scoliosis Treated With a Vertebral Column Resection: Results From an SRS Global Outreach Site (FOCOS) in Ghana. Issue 7 (August 2018) - Verma, Kushagra; Slattery, Casey; Duah, Henry; Yankey, Kawdwo P.; Mundis, Gregory; Boachie-Adjel, Oheneba
Abstract : Background: Early-onset scoliosis (EOS) remains a challenging pediatric spine condition to manage. Some severe deformities can be managed with a vertebral column resection (VCR), which is fraught with high complication rates and the outcomes have not been well reported. The purpose of this study is to provide an assessment of operative, radiographic, and clinical outcomes from children diagnosed with severe EOS treated with a VCR. Methods: We performed a retrospective review of prospectively collected data. Basic demographic data was collected along with the diagnosis, procedure performed, FOCOS risk score, blood loss (estimated blood loss), operative time, neuromonitoring events, intraoperative complications, and clinical follow-up. Coronal and sagittal radiographic parameters were measured by the first author. Results: We identified 14 patients with posttuberculosis deformity (n=7) or congenital deformity (n=7) that underwent VCR between 2013 and 2016 (5 female; age, 7.7±3 y; body mass index, 17.7±2.8). There was significant improvement in coronal radiographic parameters (primary curve: 55 to 21 degrees, secondary: 37 to 13 degrees, T1-12 length: 137 to 151 mm, T1-S1 length: 219 to 271 mm, P <0.05) and sagittal parameters (kyphosis: 85 to 41 degrees, compensatory lordosis 56 to 39 degrees, P <0.001). There was no change in chest width, sagittal vertical axis, or pelvic tilt. Mean proximal junctional kyphosis (PJK) angle was 12±9 degrees and distal junctional kyphosis angle was 9±17 degrees. Estimated blood loss was 860±520 mL and operative time was 200±66 minutes. Seven cases had neuromonitoring changes that improved with corrective maneuvers and blood pressure elevation. Three patients required reoperation for junctional breakdown with 1 having a third operation for an infection, while 2 additional patients had evidence of radiographic PJK. Conclusions: VCR in the setting of EOS has excellent radiographic outcomes but a high complication profile. Half of these cases had neuromonitoring changes intraoperatively that improved without lasting neurological deficit. Three patients had PJK and 1 had an infection requiring reoperation. Level of Evidence: Level IV—case series.